2014
DOI: 10.1021/jo501857k
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Closing Metathesis and Glycosylation Reactions: Synthesis and Biophysical Studies of Polyether-Linked Carbohydrate-Based Macrocyclic Nucleosides

Abstract: Bis-, tris-, and tetrakisuracil-substituted 12-, 13-, 17-, and 21-membered macrocyclic nucleoside analogues with polyether linkages, including C2-symmetric molecules, have been synthesized through coupling of two appropriately allylated sugar derivatives, derived from D-glucose, followed by a sequential ring-closing metathesis reaction using Grubbs catalysts, double-bond reduction, and nucleoside base insertion under Vorbrüggen reaction conditions. Spectroscopic studies on the interaction of these nucleoside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The synthesis of the per-methylated analog was initiated from the known hexa-O-methylsucrose 11 (11) which was protected at the 'fructose end' (C-6') with TBDPS-Cl. The resulting alcohol 12 was converted into phosphonate 13 and separately into aldehyde 14 according to the methodology already applied in the synthesis of the benzylated analog.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the per-methylated analog was initiated from the known hexa-O-methylsucrose 11 (11) which was protected at the 'fructose end' (C-6') with TBDPS-Cl. The resulting alcohol 12 was converted into phosphonate 13 and separately into aldehyde 14 according to the methodology already applied in the synthesis of the benzylated analog.…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrates are often used as platforms for the construction of macrocyclic receptors in optically pure form. [2][3][4][5] This refers, however, mostly to monosaccharides; [6][7][8][9][10][11] application of di-saccharides in chiral scaffolds has been rather limited. [12][13][14] Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[741]; (2) a macrocyclic amine for total synthesis of haliclorensin C [742]; (3) macrocycle-bridged oligosaccharides [743]; (4) macrocyclic ethers and macrocyclic ether-cyclophanes [744,745]; (5) macrocyclic enediynes fused to an indole ring [746]; (6) a failed attempt to prepare a macrocyclic enyne system (a Tebbe olefination was employed for synthesis of a precursor compound) [747]; (7) a macrocyclic amine-ketone for total synthesis of the ABC ring system of daphnicyclidine A [748]; (8) macrocyclic keto lactones, including those employed in total syntheses of neocosmosin A [749], and epothilone analogs [750]; (9) macrocyclic lactones [751], including those employed for syntheses of carolacton [752], the macrolactone core of Sch725674 [753], Sch725674 (also includes a cross metathesis of homoallylic alcohol and an alkene dithioacetal in an earlier event) [754], resorcyclic acid macrolactones [755], resorc [4]arene macrolactones [756], cochliomycin B and zeaenol (e.g. 302) [757], dendrodolide A (e.g.…”
Section: )mentioning
confidence: 99%
“…Examples of naturally occurring, sugar-embedded macrocycles include glycolipids (sophorolipid lactone, tricolorins, merremosides), glycophanes (cycloviracin B 1 , glucolipsin A), cyclic oligosaccharides (cyclodextrins), cyclic glycopeptides and cyclic aminoglycosides [1,5]. In recent years, carbohydrate-fused synthetic macrocycles have gained significant interest amongst synthetic chemists and they have been studied for their potential applications, particularly in biological systems [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[13]-Macrodilactones 2-6 are comprised of three four-atom planar units, a sp 3hybridized hinge atom, and asymmetric centers. It was observed that the interplay between these components gave rise to planar chirality in [13]-macrodilactones, and the handedness of the twist was determined by the absolute configuration of only one asymmetric center, at either C2 (2-5) or C7 (6), present in the macrocycles [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%